Intrinsic Resting-State Activity in Older Adults With Video Game Experience - Hou, Hai-Yan; Jia, Xi-Ze; Wang, Ping; Zhang, Jia-Xin; Huang, Silin; Li, Hui-Jie (Frontiers in Aging Neuroscience, 2019)
Playing video games is a prevalent leisure activity in current daily life, and studies have found that video game experience has positive effects in several cognitive domains. However, few studies have examined the effect of video game experience on the amplitude of low-frequency fluctuations (ALFF) among older adults. In the current study, we compared behavioral performance in the flanker task and ALFF activities of older adults, of whom 15 were video game players (VGPs) and 18 non-video game players (NVGPs). The results showed that VGPs outperformed NVGPs in the flanker task and that VGPs showed significantly increased ALFF relative to NVGPs in the left inferior occipital gyrus, left cerebellum and left lingual gyrus. Furthermore, the ALFF in the left inferior occipital gyrus and left lingual gyrus was positively correlated with cognitive performance as measured by Mini-Mental State Examination (MMSE) scores. These results revealed that playing video games might improve behavioral performance and change intrinsic brain activity in older adults. Future video game training studies in older adults are warranted to provide more evidence of the positive effects of video game experience on behavioral and brain function.